Plagiarism and Intellectual Property Rights - Heru Santoso Wahito Nugroho; Sanglar Polnok; Suparji Suparji; Winarko Winarko; Tanko Titus Auta; Budi Susatia (Alliance oh Health Activists (AloHA), 2024)
Plagiarism is an act intentionally or unintentionally in obtaining or trying to obtain credit or value for a scientific work, in an improper manner, which may be carried out by individuals, groups or institutions. Plagiarism is academic dishonesty so it is an unethical act in carrying out scientific activities. The practice of plagiarism can be suppressed by developing information literacy skills for academics and scientists. Ideally, plagiarism prevention is implemented as an integrated program with other more macro and strategic programs and involves all relevant parties. Keywords: plagiarism; prevention; intellectual property rights